ANALYSIS OF FACTORS AFFECTING LABOR PRODUCTIVITY PALM OIL HARVESTERS AT PT. PERKEBUNAN NUSANTARA IV REGIONAL II BAH BIRUNG ULU GARDEN - Jansardo Damanik; Tifany Zia Aznur; Megawati Siahaan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The productivity of oil palm harvesters is an important factor in supporting the achievement of production targets of plantation companies. This study aims to analyze the effect of premiums, work experience, age, and number of dependents on the productivity of oil palm harvesters in Afdeling III Kebun Bah Birung Ulu PT Perkebunan Nusantara IV Regional II. The study used a quantitative method with a saturated sample of 35 harvesters. Data were analyzed using multiple linear regression through the classical assumption test, t-test, F-test, and coefficient of determination (R²). The results showed that partially premiums and work experience had a positive and significant effect on labor productivity, while age had a negative and significant effect. The number of dependents did not have a significant effect on labor productivity. Simultaneously, premiums, work experience, age, and number of dependents had a significant effect on labor productivity. The coefficient of determination (R²) value of 0.737 indicates that 73.7% of the variation in labor productivity can be explained by the research variables, while the remaining 26.3% is influenced by other factors outside the model. The research results confirm that increasing premiums and work experience are the main factors that can increase the productivity of palm oil harvesting workers.